2019
DOI: 10.1002/aps3.1232
|View full text |Cite
|
Sign up to set email alerts
|

Temperature controls phenology in continuously flowering Protea species of subtropical Africa

Abstract: Premise of the Study Herbarium specimens are increasingly used as records of plant flowering phenology. However, most herbarium‐based studies on plant phenology focus on taxa from temperate regions. Here, we explore flowering phenologic responses to climate in the subtropical plant genus Protea (Proteaceae), an iconic group of plants that flower year‐round and are endemic to subtropical Africa. Methods We present a novel, circular sliding wind… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 66 publications
0
22
0
3
Order By: Relevance
“…One result of this general warming trend is changes in the timing of the onset of seasons, including the arrival of spring (Groffman et al., ; Wilson, ). In response to this warming, some species have adjusted the timing of life history events including egg hatching, migrations, flowering, and fruiting (Badeck et al., ; Forrest et al., ; Wipf, ; Hänninen and Tanino, ; Wilson, ; Hansson et al., ; Bertin, ; Jacques et al., ; CaraDonna et al., ; Groner et al., ; McDonough MacKenzie et al., ; Rice et al., ; Daru et al., ).…”
mentioning
confidence: 99%
“…One result of this general warming trend is changes in the timing of the onset of seasons, including the arrival of spring (Groffman et al., ; Wilson, ). In response to this warming, some species have adjusted the timing of life history events including egg hatching, migrations, flowering, and fruiting (Badeck et al., ; Forrest et al., ; Wipf, ; Hänninen and Tanino, ; Wilson, ; Hansson et al., ; Bertin, ; Jacques et al., ; CaraDonna et al., ; Groner et al., ; McDonough MacKenzie et al., ; Rice et al., ; Daru et al., ).…”
mentioning
confidence: 99%
“…This can influence conclusions drawn from analyses of such non-randomly sampled collections records (Syfert et al, 2013). Temporal data is increasingly used in a wide range of applications in ecology and evolutionary studies including tracking changes in phenology -the timing of seasonal events such as flowering, leafing, and fruitingand monitoring the spread of invasive species (Iler et al, 2013;Veeneklaas et al, 2013;Daru et al, 2019;Meerdink et al, 2019). Yet, while there is general agreement that climate change can influence phenological patterns by disrupting the timing of life cycle events and consequently drive changes in fitness and population demography (Ovaskainen et al, 2013;CaraDonna et al, 2014;Thackeray et al, 2016;Kharouba and Wolkovich, 2020), most have been observed in terrestrial species and to a lesser extent in marine flowering plants.…”
Section: Biases In Temporal Samplingmentioning
confidence: 99%
“…However, ectomycorrhizal fungal richness was found to have a positive association with tree species richness and saprotrophic fungal richness was not. Daru et al (2019) examined a taxonomically understudied taxon, Protea L., in a phenologically understudied part of the world-subtropical Africa. Importantly, they found that even these botanically unique Protea species respond phenologically to temperature in ways that are similar to northern temperate species.…”
Section: Emerging Frontiers In Phenological Researchmentioning
confidence: 99%
“…Daru et al. () examined a taxonomically understudied taxon, Protea L., in a phenologically understudied part of the world—subtropical Africa. Importantly, they found that even these botanically unique Protea species respond phenologically to temperature in ways that are similar to northern temperate species.…”
mentioning
confidence: 99%
See 1 more Smart Citation